Indonesian Cultural Values as Pillars of Academic Resilience: A Study on Indonesian Higher Education Students - Kaloeti, Dian Veronika Sakti; Kurnia S, Ayu; Swandi, Ni Luh Indah Desira; Lufityanto, Galang; Indrawati, Nur Diana (Indonesian Values and Character Education Journal, 2024)
This study identifies the challenges faced by students in higher education, which require academic resilience to overcome effectively. The study aims to analyze the role of local Indonesian values, such as "gotong royong" (mutual cooperation), "tawakall" (trust in God), and "kesederhanaan" (simplicity), in shaping students' academic resilience. The research method employed is a qualitative approach using focus group discussions, involving 82 undergraduate students from three major cities in Indonesia. Data collection was conducted through guided group discussions that explored students' experiences and perspectives on academic resilience. Data analysis was carried out thematically to uncover the contributions of local values to academic resilience, such as perseverance, adaptability, and problem-solving skills. The findings of the study indicate that local Indonesian values play a crucial role in shaping students' academic resilience by providing a foundation for perseverance and adaptability. The study also discusses the importance of integrating local values into educational practices and research at universities to create a resilient academic environment. The conclusion of this study is that collaborative efforts among university stakeholders are essential to promoting local values in strengthening students' academic resilience.